A Simple Study on Weight and Height of Students - Islam, Mohammad Rafiqul; Shafique, Ishraque Bin; Rahman, Kowshikur; Haque, Arafat (European Scientific Journal, ESJ, 2017)
This study was conducted on a group of male and female students of age range of 18-25 years. In this paper it is tried to find out a correlation between height and weight of male and female students. Then the simple regression equations of weight on height are fitted for both for male and female students. A total of 639 students of different departments of BRAC University, Dhaka, Bangladesh in the spring semester of 2016 are participated in this survey. Body Mass Index (BMI) of the students was calculated to compare the health status of male and females students. It is found that that the most of the students (males and females) have the normal weight. It is interestingly noticed that the higher percentage (34.18%) of males are overweight than the females; whereas the females (13.33%) are more than double in underweight than their male’s counterpart (5.93%). The correlation between height and weight of male students is calculated as 0.435 (Pearson’s coefficient of correlation). On the other hand the correlation between height and weight of female students was 0.319. From the t tests, it is proved that the both the coefficients of correlation are highly statistically significant (p-value<0.01). From the simple regression equations of weight on height, it is found that the both for male and female students the effect of height on weight is almost same. It is also found that the effect of height on weight both for male and female students is highly significant (p-value<0.01).